Muscle Activity during Handwriting on a Tablet: An Electromyographic Analysis of the Writing Process in Children and Adults - Sabrina Gerth; Julia Festman (MDPI AG, 2023)
Handwriting is a complex task that includes planning the content and the execution of handwriting movements on paper or on a tool (e.g., a tablet). This execution depends on the involvement of specific muscles in the hand (distal) and arm (proximal). The present study combines the parallel recording of the writing process on tablets and the related muscle activity with electromyography to investigate the differences in handwriting movements in two groups. A total of 37 intermediate writers (third and fourth graders, mean age 9.6 years, SD 0.5) and 18 skilled adults (mean age 28.6 years, SD 5.5) participated in three handwriting tasks. The tablet data results replicate previous findings in handwriting research for the writing process. The muscle activity data reflected a differential relationship between distinct muscle activity and handwriting performance depending on the handwriting skill (intermediate or advanced writers). Furthermore, the combination of both methods revealed that skilled writers tend to involve rather distal muscles to control the pressure of the writing pen on the surface, whereas developing writers mainly use their proximal muscles to control the velocity of their handwriting movements. This research contributes to a deeper understanding of the underlying processes of handwriting and the development of efficient handwriting execution.